Glucose Oxidase Induces Cellular Senescence in Immortal Renal Cells through ILK by Downregulating Klotho Gene Expression. (25th October 2015) - Troyano-Suárez, Nuria; del Nogal-Avila, María; Mora, Inés; Sosa, Patricia; López-Ongil, Susana; Rodriguez-Puyol, Diego; Olmos, Gemma; Ruíz-Torres, María Piedad
Abstract : Cellular senescence can be prematurely induced by oxidative stress involved in aging. In this work, we were searching for novel intermediaries in oxidative stress-induced senescence, focusing our interest on integrin-linked kinase (ILK), a scaffold protein at cell-extracellular matrix (ECM) adhesion sites, and on the Klotho gene. Cultured renal cells were treated with glucose oxidase (GOx) for long time periods. GOx induced senescence, increasing senescence associated β -galactosidase activity and the expression of p16. In parallel, GOx increased ILK protein expression and activity. Ectopic overexpression of ILK in cells increased p16 expression, even in the absence of GOx, whereas downregulation of ILK inhibited the increase in p16 due to oxidative stress. Additionally, GOx reduced Klotho gene expression and cells overexpressing Klotho protein did not undergo senescence after GOx addition. We demonstrated a direct link between ILK and Klotho since silencing ILK expression in cells and mice increases Klotho expression and reduces p53 and p16 expression in renal cortex. In conclusion, oxidative stress induces cellular senescence in kidney cells by increasing ILK protein expression and activity, which in turn reduces Klotho expression. We hereby present ILK as a novel downregulator of Klotho gene expression.